KOMPETENSI TIK DAN KEHUMASAN ASN PEMERINTAH PROVINSI SULAWESI SELATAN, SULAWESI TENGGARA, MALUKU, DAN PAPUA - Darman Fauzan Dhahir (Politeknik STIA LAN Makassar, 2020)
This study aims to capture the profile and competence of functionaries in the fields of Information and Communication Technology (ICT) and Public Relations in South Sulawesi, Southeast Sulawesi, Maluku, and Papua Provinces. Current research uses quantitative and qualitative approaches. Data collection was carried out by survey methods on 280 respondents, interviews with 50 informants and FGD in four provinces in 2018. Data were collected, presented, and described using interactive analysis techniques. The results showed that on average, the functionaries studied had an undergraduate education level and were relatively young. The majority of them are General Functional Officials, not Specific Functional Officials. Their work experience in their respective fields varies from less than 1 year to more than 10 years. ICT functionaries do office work, using word, numbers, and presentation processing applications. Public relations functionaries, predominantly use word processing applications. More than half them have never attended training in their respective fields, so only a few of them who have competency certificates. Their competencies have been measured in the range of 'beginner' to 'capable' levels. The efforts that have been made by the provincial government have not been many, but each the functionaries has tried to be able to work well by self-taught learning. The Provincial Governments’ person in charge admitted that they need support from the central government in order to improve the ICT and Public Relations competencies of the functionaries.